Combined Korean medicine therapies in children with allergic rhinitis: A multi-center, observational explanatory registry trial: A study protocol. Issue 51 (23rd December 2021) - Chu, Hongmin; Jang, Bo-Hyoung; Lee, Eunkoung; Moon, Seunghwan
Abstract: Introduction: Allergic rhinitis (AR) is the third most prevalent disease in early and middle adolescence in South Korea and one of the most common allergic diseases worldwide. Due to the ineffectiveness and frequent side effects of conventional medications for AR (such as antihistamines, corticosteroids) complementary and alternative medical (CAM) therapies have been in the spotlight. Although previous clinical trials conducted on AR with CAM showed efficacy and safety, these research results have limitations in that they did not estimate the effectiveness of combining multiple interventions. In this respect, this study aims to investigate the efficacy and safety of combined Korean medicine therapy by establishing an observational registry study at 13 Korean medical clinics that specialize in treating pediatric rhinitis. Methods: This is a prospective, observational, registry study of adolescent patients with AR. After screening, eligible subjects will be allocated to the registry. The patients will undergo a 4-week treatment and a 4-week post-treatment follow-up. The primary outcome will be the change in the average total nasal symptom score evaluated from baseline to the end of treatment. The secondary outcomes will include the numerical range scale, quality of life questionnaire in Korean children with AR, and the Pediatric Allergic Disease Quality of Life Questionnaire. KiFDA 3.0 will be measured for explanatory application on adolescents. Medical cost data and characteristics of patients such as weight, height, and sex will be collected by researchers. Discussion: This is the first multi-center observational registry study to compare combined Korean medicine treatment for AR. The results of this study will shed light on the effectiveness and safety of Korean medicine treatments for the treatment of patients with AR. Trial registration: KCT0006625 (2021.09.30)/IRB approval: Kyung-hee University Institutional Review Board (approval number: KHSIRB-21-358-1 [NA]). Trial Status: Protocol version 1.2(2021.09.16).